Pollinators exert selection on floral traits in a pollen‐limited, narrowly endemic spring ephemeral - Koski, Matthew H. (American journal of botany, 2023)
Premise Floral traits are frequently under pollinator‐mediated selection, especially in taxa subject to strong pollen‐limitation, such as those reliant on pollinators. However, antagonists can be agents of selection on floral traits as well. The causes of selection acting on spring ephemerals are understudied though these species can experience particularly strong pollen‐limitation. I examined pollinator‐ and antagonist‐mediated selection in a narrowly endemic spring ephemeral, Trillium discolor. Methods I measured pollen limitation in T. discolor across two years and evaluated its breeding system. I compared selection on floral traits (display height, petal size, petal color, flowering time) between open‐pollinated, and pollen‐supplemented plants to measure the strength and mode of pollinator‐mediated selection. I assessed whether natural levels of antagonism impacted selection on floral traits. Results Trillium discolor was self‐incompatible and experienced pollen limitation in both years of the study. Pollinators exerted negative disruptive selection on display height and petals size. In one year, pollinator‐mediated selection favored lighter petals but in the second year pollinators favored darker petals. Antagonist damage did not alter selection on floral traits. Conclusions Results demonstrate that pollinators mediate the strength and mode of selection on floral traits in T. discolor. Interannual variation in the strength, mode, and direction of pollinator‐mediated selection on floral traits could be important for maintaining of floral diversity in this system. Observed levels of antagonism were weak agents of selection on floral traits.